Feeding value of whole raw soya beans as a protein supplement for beef cattle consuming low‐quality forages. Issue 1 (13th June 2017) - Arelovich, H. M.; Lagrange, S.; Torre, R.; Martinez, M. F.; Laborde, H. E.
Summary: Experiments (Exp) I and II were conducted to compare raw whole soya beans (WSB), roasted (rWSB) or other protein sources as supplements of low‐quality forages fed ad libitum to beef cattle, upon DM intake (DMI), ruminal and blood parameters, and animal performance. Exp I: treatments for wheat straw fed to four ruminally cannulated steers were (i) Control‐WS: no supplement; (ii) WSB‐WS: whole soya beans; (iii) rWSB‐WS: roasted WSB; and (iv) SBM‐WS: soybean meal–wheat midds mixture; all fed at 1.4 kg DM/day. Exp II: 12 steers grazed deferred grain sorghum (DS) receiving these treatments: (i) Control‐DS: no supplement; (ii) WSB‐DS: 1.26 kg DM/day whole soya beans; and (iii) SFM‐DS: 1.35 kg DM/day of sunflower meal. In Exp I, WS DMI resulted 47, 52 and 41% greater for WSB‐WS, rWSB‐WS and SBM‐WS, respectively, than Control‐WS ( p < .05). In Exp II, the DMI of DS was unaffected by supplementation; a substitution of DS by supplement was found for WSB‐DS ( p < .05); however, total diet and digestible DMI increased with supplementation ( p < .05). Rumen pH in Exp I remained unaffected by supplementation, but N‐NH3 as well as blood urea‐N in Exp II increased ( p < .05). In Exp II, average daily weight gains improved similarly with both supplements compared with Control‐DS. Additionally, feed‐to‐gain ratio decreased ( p < .05), being lower for WSB‐DS (8.3) vs. SFM‐DS (9.9). Roasting effects of WSB as a supplement for low‐quality forages were not detected, and all protein sources increased total diet DMI and forage utilization. Only moderate cattle weight gains could be expected for unsupplemented DS.